Analysis for 3-D morphology structural changes for underwater topographical in Culebrita Island. Issue 7 (3rd April 2023) - Zhou, Guoqing; Yang, Zheng
ABSTRACT: In order to discover how a storm impacts underwater topographic changes, the underwater terrain morphological and structural changes in Culebrita Island were analysed. Airborne bathymetry LiDAR (Light Detection and Ranging) data from the National Oceanic and Atmospheric Administration (NOAA) with a 1.0 m spatial resolution at different time intervals (2016, 2018, 2019) were used to create three-dimensional (3D) terrain models. Four types of terrain feature attributes, water depth, slope, aspect and rugosity, were analysed to investigate terrestrial structure changes caused by the storms. The variation of underwater topography at each time interval was discussed by five profiles, the volume of deposition and erosion between different water depth intervals was investigated to derive the rate of net volume change per unit area ( m 3 ( m 2 ) − 1 ), spatial patterns of underwater topography dynamics are discussed and dynamic changes in topography structure and changes in topographic erosion deposition are observed and detected. The analysis of the topographic feature attributes for each year discovered an increase in topographic complexity. Analysis of the profiles has discovered that the topographic deposition with an average rate of 0.53 m y e a r − 1 from 2016 to 2018 and an average topographic erosion rate of 0.34 m y e a r − 1 from 2018 to 2019. In addition, it is also found that the deposition was greater than erosion from 2016 to 2018, and the erosion was greater than deposition from 2018 to 2019, with a net volume change of+48794 m 3 and a net volume change rate of+0.042 m 3 ( m 2 ) − 1 . Investigation also found that such large changes in the deposition were mainly due to the sediment carried by the storms.